RANCANG BANGUN PENGGERAK ALAT JEMUR PAKAIAN OTOMATIS BERBASIS ARDUINO UNO ATMEGA328 - Rivan Lesmanto Kahimpong; Markus Karamoy Umboh; Benny Lokombanua Maluegha (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
Rain or bad weather until recently a major problem for people who have a clothesline. Typically the clothes are dried often left to travel, so do not have time to pick up a clothesline at the time of going to rain atupun was night. to address the problems raised clothesline when it rains and it was night then the need for automated control systems by making automatic clothes line actuator. By designing all the tools from the sensor light dependent resistor (LDR) as a detector of sunlight, water sensor as a detector of rain, the DC motor as a driver, and Arduino Uno as the brain of the maker of the command of the tool, it can be made a clothesline automatically to help work in lifting clothes when it rains. From the test results the tool that has been designed. The tool works every time the sensor will read the weather around, such as when the sensor does not detect the light that the circumstances surrounding the Arduino will translate as cloudiness / dark, so that the DC motor will draw a clothesline into the house. When the sensor detects sunlight LDR then Arduino will translate around the hot weather, it will come out ortomatis clothesline. Meanwhile, when the water sensor detects raindrops then be translated by Arduino as rainy weather and then the DC motor will draw a clothesline into. From these test results mover based automatic clothes drying apparatus arduino Uno ATmega328 has worked as expected and a solution lifter or a clothesline when rain was night. Keywords: Automatic clothesline, LDR Sensor, Water Sensor, Motor DC